Table of Content - - (Journal of medical and pharmaceutical sciences, 2023)
Table of Content 1. International Alliance of Urolithiasis (IAU) Guideline on percutaneous nephrolithotomy Dr. Wissam Khalid Kamal, Dr. Mahmoud Abdulaziz Alakraa 2. Perception of School Nurses in Saudi Arabia Dr. Hala Mohammed Yasin, Dr. Pilar Isla Pera, Dr. Alaa Mujallad, Dr. Carmen López Matheu 3. A community-based study of prevalence and risk factor for “Schistosoma haematobium” in Two Endemic Districts of Taiz, Yemen Dr. Abdullnasser Ahmed Al-Kabab, Dr. Einas Ibrahim El-Sheikh, Dr. Abdulla Abdu Al-Mikhlafy 4. The association between metabolic syndrome and hypothyroidism in school-aged obese children Dr. Zeina Fawaz Alkilany, Prof. Ahmad Chreitah, Dr. Youssef Zreik 5. Knowledge, Attitude and Practice of Omani Women on Breast Self-Examination in Oman: A Grounded Theory Dr. Zalikha Khamis Darwish Al-Marzouqi, Nawal Said Al-Surihi 6. The Effect of Omega-3 Medication on Autistic Children in Riyadh, Saudi Arabia Dr. Maryam Alhassan Alnami, Dr. Maram Abdulmohsen Alswayegh